2015
DOI: 10.4172/2161-0703.s3-003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the BD Onclarity? HPV Assay Using a Non-Inferiority Test

Abstract: The clinical performance of The BD Onclarity™ HPV Assay, a novel type-specific real-time E6/E7-based PCR assay, was evaluated for clinical and analytical performance using the Meijer et al. international guidelines for validation of high-risk HPV tests. Assay performance was found to be similar to the reference method, Hybrid Capture 2 (HC2, QIAGEN) using PreservCyt ® Specimens (Hologic ® , Inc.). In addition, the fully automated assay was found to have excellent intra-and inter-laboratory reproducibility (98.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 20 publications
1
31
1
1
Order By: Relevance
“…In a multicenter U.S. study of the Onclarity assay using 541 archived samples, Wright and colleagues (24) reported the sensitivity and specificity of the assay for CIN2ϩ as 90.4% (95% CI, 83 to 95%) and 76.9% (95% CI, 73 to 81%), respectively, which are lower than the values reported in the present study, i.e., 96.1% (95% CI, 94.8 to 97.4%) and 89.1% (95% CI, 87.0 to 91.2%), respectively, and also lower than those reported by Ejegod et al (5). Again, the different populations must be considered; the U.S. study involved a younger population and histological "adjudication" by a review panel of pathologists, whereas, in the study by Ejegod et al (5) and the present study, the histological results were those derived from routine practice and were not reviewed.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In a multicenter U.S. study of the Onclarity assay using 541 archived samples, Wright and colleagues (24) reported the sensitivity and specificity of the assay for CIN2ϩ as 90.4% (95% CI, 83 to 95%) and 76.9% (95% CI, 73 to 81%), respectively, which are lower than the values reported in the present study, i.e., 96.1% (95% CI, 94.8 to 97.4%) and 89.1% (95% CI, 87.0 to 91.2%), respectively, and also lower than those reported by Ejegod et al (5). Again, the different populations must be considered; the U.S. study involved a younger population and histological "adjudication" by a review panel of pathologists, whereas, in the study by Ejegod et al (5) and the present study, the histological results were those derived from routine practice and were not reviewed.…”
Section: Discussioncontrasting
confidence: 56%
“…Initial work showed the test to be reproducible and clinically applicable in a primary cervical cancer screening setting (5). However, more data on performance, particularly at a type-specific level, is required with regard to clinical applications (6)(7)(8).…”
mentioning
confidence: 99%
“…The Hybrid Capture 2 (HC2; Qiagen, Hilden, Germany) assay (2-4) and GP5ϩ/6ϩ PCR-based enzyme immunoassay (EIA) kit HPV GP HR (EIA; Diassay, Rijswijk, the Netherlands) (5-9) were the first HPV tests to be clinically validated for primary screening on the basis of longitudinal results from large screening studies (10). Testing for high-risk HPV (hrHPV) nucleic acids is also useful for triage of women with equivocal or mildly abnormal cytology for colposcopy and as a test of cure of treatment (10).Several novel HPV tests have been fully or partially validated by showing noninferiority to HC2 or EIA and high reproducibility (11), as has been extensively reviewed by Arbyn et al (10) and reported in additional studies (12)(13)(14). These tests usually detect around 14 hrHPVs in aggregate, but some provide concurrent (partial) genotype-specific information.…”
mentioning
confidence: 99%
“…Several novel HPV tests have been fully or partially validated by showing noninferiority to HC2 or EIA and high reproducibility (11), as has been extensively reviewed by Arbyn et al (10) and reported in additional studies (12)(13)(14). These tests usually detect around 14 hrHPVs in aggregate, but some provide concurrent (partial) genotype-specific information.…”
mentioning
confidence: 99%
“…It is based on type-specific E6/E7 DNA target detection using the BD Viper LT platform (BD Diagnostics, Sparks, MD, USA). The assay simultaneously detects 13 high-risk genotypes and one possibly carcinogenic HPV genotype (HPV66) (13); it provides genotyping information on six individual genotypes (16,18,31,45, 51, and 52) and reports the remaining eight HPV genotypes in three distinct groups (33/58, 56/59/66, and 35/39/68). The assay has an internal human beta globin (HBB) gene control for sample sufficiency and assay performance.…”
mentioning
confidence: 99%